Prediction Of Fundamental Factors On Quotation Prices - WIDIASTUTI, Retno (PT Keberlanjutan Strategis Indonesia, 2021)
The purpose of this study is to examine the effect of fundamental factors on stock prices and to examine differences in the effects of fundamental factors on stock prices during the period of changes in mineral export policies. Fundamental factors are proxied by earning per share (EPS), net profit margin (NPM), return on equity (ROE), return on assets (ROA), and debt to equity ratio (DER). The research object is all companies in the mining sector listed on the Indonesia Stock Exchange (IDX) during the period 2014 – 2019, with a total population of 269 observations. The sampling technique was purposive sampling, with the results of 176 observations. The observation data came from 37 companies. Methods of data analysis using multiple regression and paired t-test. The results showed that only the EPS variable did not affect stock prices. Then, the study results also show that there is no difference in the influence of fundamental factors on stock prices during the export ban period and the reopening of the raw mineral export ban. This condition illustrates that investors still have confidence in the fundamental factors reported by companies in the mining sector.